Genomic diversity, population structure, and signature of selection in five Chinese native sheep breeds adapted to extreme environments - Abied, A.; Bagadi, A.; Bordbar, F.; Pu, Y.; Augustino, S.M.A.; Xue, X.; Xing, F.; Gebreselassie, G.; Han Jianlin; Mwacharo, Joram M.; Ma, Y.; Zhao, Q. (MDPI, 2020)
Through long term natural and artificial selection, domestic sheep (Ovis aries) have become adapted to a diverse range of agro-ecological environments and display multiple phenotypic traits. Characterization of diversity and selection signature is essential for genetic improvement, understanding of environmental adaptation, as well as utilization and conservation of sheep genetic resources. Here, we aimed to assess genomic diversity, population structure, and genomic selection among five Chinese native sheep breeds using 600K high density SNP genotypes. A total of 96 animals of the five breeds were selected from different geographical locations with extremely dry or humid conditions. We found a high proportion of informative SNPs, ranging from 93.3% in Yabuyi to 95.5% in Wadi, Hu, and Hetian sheep. The average pairwise population differentiation (FST) between the breeds was 0.048%, ranging from 0.022% to 0.054%, indicating their low to moderate differentiation. PCA, ADMIXTURE, and phylogenetic tree analyses revealed a clustering pattern of the five Chinese sheep breeds according to their geographical distribution, tail type, coat color, body size, and breeding history. The genomic regions under putative selection identified by FST and XP-EHH approaches frequently overlapped across the breeds, and spanned genes associated with adaptation to extremely dry or humid environments, innate and adaptive immune responses, and growth, wool, milk, and reproduction traits. The present study offers novel insight into genomic adaptation to dry and humid climates in sheep among other domestic animals and provides a valuable resource for further investigation. Moreover, it contributes useful information to sustainable utilization and conservation of sheep genetic resources.